The limits of self-governance in the presence of spite: experimental evidence from urban and rural Russia - Simon Gächter; Benedikt Herrmann (Institute for the Study of Labor (IZA), 2006)
We report evidence from public goods experiments with and without punishment which we conducted in Russia with 566 urban and rural participants of young and mature age cohorts. Russia is interesting for studying voluntary cooperation because of its long history of collectivism, and a huge urban-rural gap. In contrast to previous experiments we find no cooperation-enhancing effect of punishment. An important reason is that there is substantial spiteful punishment of high contributors in all four subject pools. Thus, spite undermines the scope for self-governance in the sense of high levels of voluntary cooperation that are sustained by sanctioning free riders only.
Keywords: H41; C91; D23; C72; 330; social norms; free riding; punishment; spite; experiments